Complex regional pain syndrome (CRPS) (Journal of Health Sciences, 2015)
Complex regional pain syndrome (CRPS), once known as reflex sympathetic dystrophy, Sudeck's dystrophy and causalgia, is a pain syndrome with indistinctive pathophysiology and unpredictable clinical course. CRPS can develop after a limb fracture, injury or damage to the peripheral or central nervous system. The diagnosis of CRPS is based on the signs and symptoms obtained from the medical history and physical examination. The disease is often resistant to treatment, and its course is not always favorable. A brief overview of this clinical entity is presented, and most relevant and up-to-date information is discussed.